Answer:
Step-by-step explanation:
(9x-1)^-1/2 - (x+2)(9x-1)^-1/2
= (9x-1)^-1/2( 1 - (x + 2))
= (9x-1)^-1/2(-1 - x)
= -(x + 1)(9x-1)^-1/2
= -(x + 1) / (9x-1)^1/2
Answer:
No
Explanation:
75 x 6.75 ÷ 100 = 5.0625
75 + 5.0625 = 80.0625
80.0625 = 80.06$
Answer:
The following equation is not a circle, but a hyperbola, because you have 4y, but no y^2
Step-by-step explanation:
Please mark for Brainliest!! :D Thanks!!
For more questions or more information, please comment below!
C. 2/3 is the correct answer. I worked this question out and that is what I got! I hope you have a nice day! (mark as brainliest!)
By substitution
f(6) = 1.8×2^(6)
= 1.8×64
= 115.2